GERAKAN POJOK PROMKES REMAJA SEHAT DAN PRODUKTIF DALAM PENCEGAHAN PENYAKIT TIDAK MENULAR DI KELURAHAN LEGOK DANAU SIPIN KOTA JAMBI - Triana, Winda; Sayuti, Solihin; Nopindra, Alpari (Jurnal Salam Sehat Masyarakat (JSSM), 2023)
Non-Communicable Diseases (NCDs) are the highest cause of death in Indonesia. The development of NCDs is increasing due to trends and shifts in disease patterns. Adolescents are at risk of developing NCDs due to risky behavior in unhealthy living habits, such as smoking, alcohol, drugs, unhealthy reproduction and eating patterns, and lack of physical activity. Mitra Ayu District Health Center's priority problem is the high number of NCDs such as hypertension, diabetes mellitus, cholesterol and high blood pressure. Partner location data includes teenagers who use drugs, smoke, drink alcohol and marry early. The aim of community service is to increase teenagers' knowledge using poster media containing health material which is stored in a QR barcode link, posted in public places such as schools, village heads' offices, babinsa, motorbike taxi bases, health centers, and in residents' homes. At any time, residents who want to read can scan where posters and health educational videos will appear that can be read with ever-increasing material. The activities carried out in community service are gymnastics together with physical activities, planting toga, health checks namely blood pressure, sugar, cholesterol, together with 5 health program students carrying out health education about drugs, smoking, reproductive organs and the impact of free sex. Education in partnership with BNN, Putri Ayu Community Health Center midwives. Processing fish resources, making crispy ikan bilis and making compost from water hyacinth leaves in partnership with UKM Paddle Habibah. To measure the success of measuring instrument education, it is done through the pre-test and post-test stages using a knowledge variable questionnaire with a target of 200 respondents, carried out between January and October 2023. The results of the education were an increase in mean pre-test knowledge (6.92) and mean post-test (13.97), an increase in scores. knowledge of 7.05. It is recommended that sub-districts continue physical activities every Sunday together at the sub-district head's office, that the Community Health Center facilitate regular health checks so that NCDs are detected, the community is aware and willing to monitor healthy behavior by always reading the material on the PTM barcodes that have been posted in public places. , UKM Dayung Habibah can continue making crispy ikan bilis to improve the family economy, as well as developing more modern composting for water hyacinth raw materials.